Exploring Narrative Structure and Hero Enactment in Brand Stories - Sanders, José; van Krieken, Kobie (Frontiers in Psychology, 2018)
This study examines how audiovisual brand stories both invite and enable consumers to enact heroic archetypes. Integrating research on the archetypal structure of narratives with research on the event structure of narratives, we distinguish singular plot stories (i.e. stories that show a Hero’s Journey) from embedded plot stories (i.e. stories that not only show but also tell one or more Hero’s Journeys) and develop a conceptual and narratological framework to analyze their structural elements. Application of the framework to 20 brand stories representing 8 different brands reveals meaningful variation in elements between the singular plot stories and embedded plot stories. Differences in the expression of archetypes and event structure are argued to evoke different types of Hero enactment which in turn result in different outcomes. We specifically hypothesize that the enactment of heroic archetypes in singular plot stories primarily results in catharsis (pleasure), whereas the enactment of heroic archetypes in embedded plot stories primarily results in an outcome we describe as phronesis: a form of moral sense making of the self that advances one’s practical wisdom and prudence. The final section of the paper discusses how cathartic and phronetic outcomes of hero enactment may foster the psychological bonding between brand and consumer, and invite consumers to align their moral values with the values that are reflected by heroic character traits. The central aims of the analysis presented are to provide an exploration of narrative phenomena in a reasonably broad range of brand story videos and foremost to provide a conceptual framework with an applicable instrument suited to analyze relevant categories in these brand stories. The present study is interdisciplinary in its approach to a contemporary, developing marketing phenomenon, applying psychological modeling of archetypes and heroic values with narratological insights on perspective-taking and story structure. Its contribution is to systemize, from a narratological viewpoint, how various narrative archetypes in brand video stories may contribute to the development of brand-consumer relations.